Pengembangan Multimedia Interaktif Berbasis Smart Application Creator (SAC) Pada Pembelajaran IPAS di Kelas IV Sekolah Dasar - Wikimalzis, Wikimalzis; Zuardi, Zuardi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
This research was conducted due to the lack of use of IT-based interactive learning media that are relevant to the times, as well as the lack of variety in learning media. This research uses a Research and Development (R&D) approach by applying the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. With an average learning media validity of 92.7%, specific material validity of 90%, language validity of 96%, and media validity of 92.1%, the final output is considered quite valid. With an average of 95.5% and 96.1% for teacher and student answers, respectively, effectiveness category results resulted in an average of 92.2% for effectiveness results. Therefore, it can be said that the use of interactive multimedia based on Smart Application Creator in social studies classes in elementary schools for grade IV has proven to be a valid, practical, and effective learning medium.